Evaluation of microhardness of short fiber-reinforced composites inside the root canal after different light curing methods – An in vitro study - Fráter, Márk (Netherlands, 2026)
Objectives: Short fiber-reinforced composite (SFRC) materials make it possible to reinforce root canal treated teeth with individualized, directly layered intraradicular posts (the Bioblock technique). The question arises, however, as to whether the photopolymerization of the material is sufficient deep within the root canal space and if it can be improved through different light-conducting options. Our study aimed to investigate the hardness of intraradicular SFRC material applied using the Bioblock technique and cured with various illumination methods, as measured through nanoindentation.
Materials and methods: For this investigation, thirty plastic artificial teeth that had undergone root canal treatment were selected. These teeth were randomly divided into six study groups (Group 1-6; each group consisting of 5 teeth). The restoration procedures involved the use of SFRC or conventional composite materials, placed 6 mm apically from the root canal orifice. In Group 1 and 2, a conventional composite was used, whereas in Group 3-6, SFRC was employed for interradicular reinforcement (with a layered technique in Group 3 and 4 and a bulk-fill technique in Group 5 and 6). A modified light source was utilized for photopolymerization in Group 2, 4, and 6, whereas in Group 3 and 5, the polymerization light was directed through a prefabricated glass fiber posts. The control group (Group 1) utilized conventional composite material with a standard light-curing method. Following embedding and sectioning, the hardness of the composite materials was measured at 2 mm intervals within the root canal (1st, 2nd, 3rd measurements, in the coronal to apical direction).
Results: During the 1st measurement, light curing conducted through the glass fiber posts (Group 3 and 5) led to markedly higher hardness levels compared to the groups restored with conventional composite (control group with p = 0.002, p = 0.001, and Group 2 with p = 0.043, p = 0.034, respectively). In the 2nd measurement, only Group 5 demonstrated significantly greater hardness in comparison to the control group (p = 0.003) and Group 2 (p = 0.015). However, in the 3rd measurement, no statistically significant differences were observed among the groups.
Conclusion: light curing through the glass fiber post provides outstanding hardness for the SFRC material in the apical layer in the root canal.